Primary Anorectal Amelanotic Melanoma: Case Report and Review of Literature - Maharjan, Sailuja; Satyal, Bandana; Baidya, Reena; Neupane, Prakash Raj (Nepalese Journal of Cancer, 2022)
Primary amelanotic melanoma of rectum is a very rare tumor accounting for less than 2% of melanomas. It is a highly aggressive tumor that often tends to invade lymph nodes or metastasize in the early course of disease. The prognosis of this tumor is very bismal with five year survival of less than 20%. We report a case of primary amelanotic melanoma of anorectum in which preoperative biopsy was inconclusive, thus highlighting the role of immunohistochemical markers to reach to a correct diagnosis. This is the first case of amelanotic anorectal melanoma reported from Nepal.